Immunopsychiatry : a clinician's introduction to the immune basis of mental disorders - Teixeira, Antonio L.; Bauer, Moises E. ([New York] : Oxford University Press, 2019)
This text assembles and presents the available data on the immune/inflammatory dysfunction in psychiatric disorders, indicating the potential of immune mechanisms as either biomarkers or therapeutic targets, as well as discussing the challenges ahead of incorporating this knowledge into clinical practice.
Previously issued in print: 2018.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on January 4, 2019).
Keywords: Psychiatry; Neuroimmunology